2021
DOI: 10.1016/j.livsci.2020.104343
|View full text |Cite
|
Sign up to set email alerts
|

The effects of manual and automated milk feeding methods on group-housed calf health, behaviour, growth and labour

Abstract: This article is made publicly available in the institutional repository of Wageningen University and Research, under the terms of article 25fa of the Dutch Copyright Act, also known as the Amendment Taverne. This has been done with explicit consent by the author.Article 25fa states that the author of a short scientific work funded either wholly or partially by Dutch public funds is entitled to make that work publicly available for no consideration following a reasonable period of time after the work was first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 40 publications
3
18
0
Order By: Relevance
“…Calf-level outcomes for heifer calves on study farms were broadly consistent with the findings of other Irish studies, with most calves having a score of 0 for all parameters, i.e., they were healthy [ 20 , 21 ]. The median age of heifers during the first sampling period was 39 days, just outside the consensual definition of the neonatal period of 30 days [ 22 ].…”
Section: Discussionsupporting
confidence: 82%
“…Calf-level outcomes for heifer calves on study farms were broadly consistent with the findings of other Irish studies, with most calves having a score of 0 for all parameters, i.e., they were healthy [ 20 , 21 ]. The median age of heifers during the first sampling period was 39 days, just outside the consensual definition of the neonatal period of 30 days [ 22 ].…”
Section: Discussionsupporting
confidence: 82%
“…This may be due to feeding method rather than housing system. This is confirmed by Sinnott et al (2021) who showed large differences exist in the labor associated with manual feeding twice a day and automatic feeding systems for indoor group-reared calves, indicating labor efficiencies may be closely related to feeding systems rather than housing system.…”
Section: Introductionmentioning
confidence: 60%
“…The high labor requirement for calf rearing, particularly on seasonal calving farms, has resulted in increased interest in using technology and automation to reduce the labor requirement associated with calf rearing. Automatic calf feeding systems are increasing in popularity primarily due to claimed economic gains arising from labor savings [91]. Increased feeding frequency, gradual weaning and socialization benefits for the calf [92] means that automated feeding can come closer to mimicking the way calves feed and behave in nature, potentially increasing animal welfare.…”
Section: (P 1461)mentioning
confidence: 99%